Initial Vocabulary Analysis of Nouns in the Field of Legal Studies - Sri Utami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this research is to analyze initial vocabulary of nouns in the field of Legal Studies had by the first semester students of Law Study Program of University of Kutai Kartanegara in academic year 2019/2020. This study used descriptive qualitative design. The research subjects were 10 students of the first semester. The instrument of the study was vocabulary test in the form of written test by using match type test. The results of this study are as follows: (1) there were 9 words that became the most common initial vocabularies of nouns in the field of Legal Studies, (2) There were 6 words that became the most unfamiliar nouns for almost all the students. Based on the findings of the research it could be summarized (1) the initial vocabularies of nouns in the field of Legal Studies were varies but still very limited; (2) the nouns in the field of Legal Studies that were not familiar for the students were also varies. It meant that each student has different familiar and unfamiliar nouns. The initial vocabularies of nouns in the field of Legal Studies had by the students were different one each other. Some students had more initial vocabularies but some others had less initial vocabularies. Keywords: initial vocabularies, nouns, legal studies